Animal models to study pathogenesis and treatments of cardiac disorders in rheumatoid arthritis: Advances and challenges for clinical translation. (August 2021) - Kessler, Julie; Totoson, Perle; Devaux, Sylvie; Moretto, Johnny; Wendling, Daniel; Demougeot, Céline
Abstract: Although cardiac diseases such as acute myocardial infarction, heart failure and arrhythmias are the leading cause of cardiovascular complications in rheumatoid arthritis (RA), their pathogenesis is far from being understood and optimal therapeutic options to treat specifically these disorders in RA are lacking. Preclinical studies on animal models of arthritis can help to decipher the complex link between arthritis and the heart, and to identify critical pathways and novel therapeutic targets. This review presented the available data on cardiac disorders in animal models of RA, as well as the current knowledge on pathophysiology and pharmacology of these disorders. Future directions for translational studies in a cardiorheumatic perspective are proposed. Highlights: Rat models of arthritis reproduce structural / functional cardiac disorders of RA. Inflammation and oxidative stress appear as the cornerstone of heart impairments. These models are suitable for pharmacological research. More studies are needed on models of genetically engineered or chronic arthritis.